Properties and applications of nanoclay reinforced open-porous polymer composites - Yuce, Elif; Mert, E. Hilal; Sen, Sinan; Saygi, Semih; San, Nevim (WILEY, 2017)
Open-porous nanoclay reinforced polymer composites were prepared via high internal phase emulsion templating using 1,3-butanediol dimethacrylate and surface modified montmorillonite (SM-MMT). Organophilic clay was obtained by using a reactive intercalantquaternary cocoamine salt having a styryl groupfor surface modification of MMT. The clay modification resulted in not only intercalated silicate layers but also nanoclay particles compatible with the continuous phase of the emulsions. It was found that increasing clay amount leads to formation of hierarchical porous structure accompanied with larger cavities and interconnected pores. In this respect, cavity size of the resulting composites was found to be altered between 6.78 and 8.82 m. On the other hand, as compared to bare composites, addition of clay particles increased compressive modulus of the resulting materials from 26.4 to 72.5 MPa. The adsorption capacities of the porous composites for methyl violet 2B were investigated by batch experiments and discussed as a function of their SM-MMT loading. It was determined that, the dye adsorption of the composites increased with increasing nanoclay amount in the polymer matrix. Thus, the adsorption percentage of the composite loaded with 7 wt % nanoclay was found to be as high as 88%. (c) 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45522.
Keywords: adsorption; clay; mechanical properties; morphology; porous materials; METHYL VIOLET 2B; GLYCIDYL METHACRYLATE; MECHANICAL-PROPERTIES; POLYHIPE MONOLITHS; FOAMS; KINETICS; SCAFFOLDS; ISOTHERM; REMOVAL; Polymer Science